Frequency Specificity of fMRI in Mesial Temporal Lobe Epilepsy - Song, Shuyan; Ding, Mingyue; Li, Hong; Song, Xiaopeng; Fan, Wenliang; Zhang, Xuming; Xu, Haibo (PLOS ONE, 2016)
Medial temporal lobe epilepsy (mTLE) is a system-level disease characterized by aberrant neuronal synchronization and widespread alterations in function. Previous studies have focused on the amplitude analysis of the blood oxygenation level-dependent (BOLD) signals to reveal the aberrant alterations in mTLE. However, these methods did not work well in the cases where the amplitudes of two oscillations are correlated but the underlying oscillations are neither phase coherent nor frequency consistent. To address this problem, we investigated the differences of frequency specificity between patients with mTLE and healthy controls using the extreme-point symmetric mode decomposition (ESMD) method. In this method, the BOLD signals were decomposed into a set of intrinsic mode functions (IMFs) and the instantaneous frequency of each IMF was calculated using the direct interpolation strategy. The intrinsic frequency (denoted as Freq) for every voxel was obtained by the weighted sum of the instantaneous frequencies of all the IMFs. The Freq was used as an index to evaluate the altered frequency specificity of 41 patients with mTLE (17 right-side, 24 left-side) and 24 healthy control subjects. The results show that the peak of frequency distribution curve for the patients moves towards the higher frequency than that for the healthy controls. Compared with the healthy control group, the patients with left mTLE demonstrate higher Freq in the default mode network, middle frontal gyrus, insula, middle temporal gyrus and calcarine gyrus; the patients with right mTLE demonstrate higher Freq in the precuneus and occipital lobe. For the three groups, the distinct frequency distribution appears in the left and right hippocampus due to the hippocampal structural and functional asymmetries. The preliminary results imply that the frequency-specific correlated oscillations in the distributed brain regions can provide information about the nature of diseases affecting the brain and the alterations of frequency specificity are associated with the pathological characteristics of mTLE.